Synthesis, Crystallography, and Anti-Leukemic Activity of the Amino Adducts of Dehydroleucodine - Paola E. Ordóñez; David E. Mery; Krishan K. Sharma; Saumyadip Nemu; William F. Reynolds; Raul G. Enriquez; Darcy C. Burns; Omar Malagón; Darin E. Jones; Monica L. Guzman; Cesar M. Compadre (Molecules, 2020)
Dehydroleucodine is a bioactive sesquiterpene lactone. Herein, four dehydroleucodine amino derivatives were synthesized using the amines proline, piperidine, morpholine, and tyramine, and spectroscopic methods and single-crystal X-ray diffraction unambiguously established their structures. The cytotoxic activity of these compounds was evaluated against eight acute myeloid leukemia cell lines, and their toxicity to peripheral blood mononuclear cells was also determined. The proline adduct was the most active compound, it showed anti-leukemic activity, upregulated heme oxygenase 1 (HMOX1) and the primary stress-inducible isoform of the heath shock 70 kDa protein 1 (HSPA1A), and downregulated NFkB1 transcription, it was also found to be about 270 times more water soluble than dehydroleucodine.